Guru Sebagai Agen Konseling: Upaya Penanganan Stres Akademik Siswa di SMAN 1 Palangka Raya - Meliny Meliny; Surawan Surawan (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2025)
This research examines the role of teachers as counseling agents in managing academic stress among students at SMAN 1 Palangka Raya. In the context of increasing academic demands, students often experience psychological pressure that negatively impacts their mental health and performance. This study employs qualitative methods, including observations and in-depth interviews, to identify teachers' roles in detecting stress symptoms and providing emotional support. The findings reveal that teachers can implement adaptive teaching methods and create a comfortable classroom atmosphere, helping students cope with stress. The implications of this research emphasize the importance of collaboration among teachers, parents, and school counselors in creating a healthy learning environment that supports both academic and psychosocial development of students comprehensively.